Playing strategically against nature? Decisions viewed from a game-theoretic frame - Martin Beckenkamp (Max Planck Institute for Research on Collective Goods, 2008)
Common research on decision-making investigates non-interdependent situations, i.e., games against nature. However, humans are social beings and many decisions are made in social settings, where they mutually influence each other, i.e., strategic games. Mathematical game theory gives a benchmark for rational decisions in such situations. The strategic character makes psychological decision-making more complex by introducing the outcomes for others as an additional attribute of that situation; it also broadens the field for potential coordination and cooperation problems. From an evolutionary point of view, behavior in strategic situations was at a competitive edge. This paper demonstrates that even in games against nature, people sometimes decide as if they were in a strategic game; it outlines theoretical and empirical consequences of such a shift of the frame. It examines whether some irrationalities of human decision-making might be explained by such a shift in grasping the situation. It concludes that the mixed strategies in games against nature demand a high expertise and can only be found in situations where these strategies improve the effects of minimax-strategies that are used in cases of risk-aversion.
Keywords: 300; Entscheidung; Verhaltensökonomik; Spieltheorie; Framing; Test